2022
DOI: 10.1002/aelm.202200816
|View full text |Cite
|
Sign up to set email alerts
|

Protons: Critical Species for Resistive Switching in Interface‐Type Memristors

Abstract: Fe 2 O 3 , VO 2 ) and perovskite oxides (e.g., SrTiO 3 , BaTiO 3 , SrZrO 3 ) have been widely explored for RS and related applications. [5][6][7][8] Significant improvements have been made in memristor technology by realizing large on/off ratio, fast switching, excellent retention, low read/ write voltage, and integration with complementary metal-oxide semiconductor technology. [5,[9][10][11] In general, there are two types of memristive switching devices: filamenttype (FT) and interface-type (IT). Most of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…[ 36,37 ] A detailed study on the RS mechanisms in the Au/Nb:STO interface‐type device is presented in our previous work, which explored the critical roles of protons (from moisture) in charge trapping/detrapping and Schottky barrier modulation. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 36,37 ] A detailed study on the RS mechanisms in the Au/Nb:STO interface‐type device is presented in our previous work, which explored the critical roles of protons (from moisture) in charge trapping/detrapping and Schottky barrier modulation. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…t \left.\right) \textrm{ } \alpha \textrm{ } t^{- 0.06}$ at 0.4 V. [ 36 ] This minor current decay may be due to the progressive trapping of charges which were detrapped during the set process. [ 34 ] As the negative read voltage promotes charge trapping process, LRS current decay was much faster with −0.4 V readout than with +0.4 V readout. The device maintained a high on/off ratio of ≈10 4 at −0.4 V and 10 5 at 0.4 V. The performance of the Au/Nb:STO IT devices was comparable or even better than that of some other metal oxide‐based FT memristors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also reported that charge trapping and de-trapping mechanism is related to protons/moisture. [65] Therefore, it is possible that multiple sources contribute to the overall switching process.…”
Section: J a T Q Ktmentioning
confidence: 99%